Polymeric dental composites based on remineralizing amorphous calcium phosphate fillers - Skrtic, Drago (Curr Trends Polym Sci, 2016)
For over two decades we have systematically explored structure-composition-property relationships of amorphous calcium phosphate (ACP)-based polymeric dental composites. The appeal of these bioactive materials stems from their intrinsic ability to prevent demineralization and/or restore defective tooth structures via sustained release of remineralizing calcium and phosphate ions. Due to the compositional similarity of the ACP to biological tooth mineral, ACP-based composites should exhibit excellent biocompatibility. Research described in this article has already yielded remineralizing sealants and orthodontic adhesives as well as a prototype root canal sealer. Our work has also contributed to a better understanding on how polymer matrix structure and filler/matrix interactions affect the critical properties of these polymeric composites and their overall performance. The addition of antimicrobial compounds to the formulation of ACP composites could increase their medical and dental regenerative treatment applications, thereby benefiting an even greater number of patients.